2022
DOI: 10.1186/s12913-022-07800-1
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of young people’s, parent/carers’, and professionals’ experiences of a voluntary sector organisation operating a Youth Information, Advice, and Counselling (YIAC) model in a disadvantaged area

Abstract: Background The present evaluation explored young people’s, parents/carers, and healthcare professionals’ perceptions of the Youth Information, Advice and Counselling (YIAC) model operated by a voluntary sector organisation in North West England. With an aim to understand the key components that contribute to enhancing the success of the YIAC model. Method Semi-structured interviews and focus groups with young people, parents/carers, and healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The importance that participants placed on rapid access to support in order to prevent the deterioration of CYP’s mental health resonates with previous studies [ 27 , 49 ]. Indeed, it has been reported that the longer CYP spend on a waiting list the more likely they are not to engage with services [ 41 ], and that rapid access is associated with increasing their motivation to engage in therapeutic work [ 50 ].…”
Section: Discussionsupporting
confidence: 59%
“…The importance that participants placed on rapid access to support in order to prevent the deterioration of CYP’s mental health resonates with previous studies [ 27 , 49 ]. Indeed, it has been reported that the longer CYP spend on a waiting list the more likely they are not to engage with services [ 41 ], and that rapid access is associated with increasing their motivation to engage in therapeutic work [ 50 ].…”
Section: Discussionsupporting
confidence: 59%
“…The National Children’s Bureau [ 38 ] stressed the importance of personalising services and therapies for CYP with poor mental health. Finally, Hassan et al [ 39 ] report on a specific service model, Youth Information, Advice and Counselling Services (YIACS; categorised as a C3 model in our typology). Hassan et al identified opportunities to self-refer, timely provision of support, non-clinical environments, age-appropriate services (personalisation), a non-hierarchical workforce (learning culture) and interagency collaboration as key facilitators of access to, and engagement with, YIACS.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the National Children's Bureau 104 stressed the importance of personalising services and therapies for CYP with poor mental health. Finally, a 2022 paper on YIACS 105 (published after our review searches had been completed) identified opportunities to self-refer, timely provision of support, non-clinical environments, age-appropriate services (personalisation), a non-hierarchical workforce (learning culture) and interagency collaboration as key facilitators of access to, and engagement with, YIACS. These factors are strikingly similar to those in our model.…”
Section: Comparing Our Model With Previous Research and Policymentioning
confidence: 99%